Impact of Earning Per Share and Dividend Per Share on Market Price of Stock - Deepak Prasad Kaphle (Journal of Balkumari College, 2025)
This research examines the factors affecting the financial influence of Standard Chartered Bank (SCB) and Nabil Bank, two senior banks listed on the Nepal Stock Exchange. This study of the relationship between market price per share (MPPS) and key financial activities such as earnings per share (EPS) and dividends per share (DPS). This research applying a quantitative methodology and applying secondary data on these variables utilizes statistical techniques, including mean, standard deviation, skewness, and kurtosis. The assess strength and direction of their relations with MPPS. This study covers a five-year period from 2076/077 to 2080/081. The results significant relationship was found in SCB (P=0.015) at 5% significant level but not significant in Nabil bank (P=0.439). It shows the indication of strong evidence that SCB’s DPS is statistically higher than Nabil’s. The findings indicate a substantial influence of EPS and DPS on stock prices. These insights are expected to provision investors in making well-informed investment decisions. The bank management assist in maximizing shareholder value and support policymakers in considering regulations and fastly the growth of Nepal’s banking sector.